Od notranjih zadev do varstvoslovja – zgodba o nastajanju in razvoju Fakultete za varnostne vede (University of Maribor Press, 2023)
From Internal Affairs to Criminal Justice and Security – the Story of the Formation and Development of the Faculty of Criminal Justice and Security. The commemorative publication "From Internal Affairs to Criminal Justice and Security – the Story of the Creation and Development of the Faculty of Criminal Justice and Security”, which celebrates fifty years of development, creation, education, research and sharing of knowledge in the field, which today is characterized by the new interdisciplinary science of criminal justice and of security, was based on testimonies of the director of the Department of Internal Affairs at the Higher School of Administration, eight deans and students, representatives of five different periods of the faculty’s development. Along with memories of the development from the former higher school up to the current Faculty of criminal justice and security of the University of Maribor, the characteristics of the study programmes and research activities are also specially presented. In addition, the library and other professional services, as well as the institution of the faculty’s executive secretary, as a pillar of the legitimacy and stability of the faculty are presented. Since the university is also a place of symbolism, the symbolic meaning of the dean’s insignia – toga and chain – is presented. The publication concludes with a presentation of the renovation of the faculty’s building, and a list of employees of the Faculty of criminal justice and security and its predecessors between 1973 and 2023.